Purity and Patriarchy in Trinidad’s Kali Mai Puja - Maharaj, Vieann Ragoonanan (Religion & gender, 2026)
This article examines gender roles and relations within Kali Mai Puja as practiced at the Jai Kali Shakti Mandir, a temple in Trinidad. The analysis focuses on women’s roles in the ritual space, views of women’s bodies, and perceptions of sexuality in matrifocal religious practice that is governed by plural patriarchal ideas. I argue that women are not afforded the same rights and privileges as men in or out of the ritual space due to practitioners’ cultural interpretations of female bodies. The deity Kali is held in reverence and deemed absolutely pure, but the material manifestations of the same deity, women, are seen as incapable of achieving purity even though they are capable of being marlos or mediums for the deity herself. Patriarchal notions of gender and power are conveyed through beliefs and practices within the religious practice and are propagated by many women who are socially conditioned to accept such notions.